2022
DOI: 10.1088/1755-1315/977/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Survey and distribution of Pineapple Wilt Mealybug Wilt associated Virus (PMWaV) on pineapple plants in North Tapanuli, Indonesia

Abstract: The authors conducted a survey of Pineapple Mealybug Wilt-associated Virus (PMWaV) on pineapple plants in four pineapple-producing sub-districts in North Tapanuli, namely Sipahutar, Pangaribuan, Siborongborong, and Tarutung. This survey aims to detect the presence and distribution of PMWaV in North Tapanuli. The survey found PMWaV in pineapple plants in all survey locations with varying symptoms such as wilting to a yellow-red colour and curling leaf tips, curling and drying leaves and leaf tips, and showing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The primary symptoms of MWP are wilting, reddish-yellow leaves beginning with the outer leaves and undersized fruit. When the symptoms are severe, the plant will likely die, the leaf tips curl and dry up, and plant growth slows down (Hutahayan et al, 2022). Although the exact cause of MWP is unknown, it is thought to be linked to specific viruses, mealybugs as vectors, ants that guard mealybugs and facilitate their spread, and environmental factors.…”
Section: Mealybug Wilt Of Pineapple (Mwp)mentioning
confidence: 99%
“…The primary symptoms of MWP are wilting, reddish-yellow leaves beginning with the outer leaves and undersized fruit. When the symptoms are severe, the plant will likely die, the leaf tips curl and dry up, and plant growth slows down (Hutahayan et al, 2022). Although the exact cause of MWP is unknown, it is thought to be linked to specific viruses, mealybugs as vectors, ants that guard mealybugs and facilitate their spread, and environmental factors.…”
Section: Mealybug Wilt Of Pineapple (Mwp)mentioning
confidence: 99%
“…Meanwhile, the leaves of plants infected with PMWaV and associated with Meloidogyne javanica experienced a decrease in turgidity [12]. MWP severity score refers to Hutahayan [13], who divides symptom severity into five severity scores. In this study, the authors chose three scores: score of 0 for healthy plants, score of 3 for moderate symptoms with a severity of 25−50%, and score of 4 for severe symptoms with a severity above 50%.…”
Section: Symptoms Of Mwp At Three Levels Of Healthmentioning
confidence: 99%
“…A study by Hutahayan et al (2022) showed the occurrence of wilt disease with symptoms of wilting, yellow-red discoloration, and leaf tip curling of pineapple plants in Pansurnatolu Village, with a severity level of up to 65% categorized as severe. Pineapple plants with wilt disease caused by PMWaV show a decrease in growth and change in leaf color to reddish chlorosis (Moreno et al (2021), and this is in keeping with the findings of de Araújo et al ( 2021) who found differences in the development of Macauba palm plants attacked by D. brevipes, where the height and canopies of the plants were lower (112.3-138.1 cm) and smaller when compared to the healthy plants (187.8-191.6 cm).…”
Section: Mealybug Samples Collectionmentioning
confidence: 99%